Good governance in microcredit strategy for poverty reduction: Focus on Western Mindanao, Philippines - Frede G. Moreno (University of the Philippines-Diliman, 2004)
Microcredit can be an effective tool for tackling the global poverty problem. Making microcredit work better for the poor necessitates a framework that integrates the principles of good governance in the design and implementation of a microcredit program. The integration of good governance principles in microfinance is argued to have positive consequences in improving financial viability and increasing social outreach of microcredit programs as well as in widening the livelihood and economic options of Agrarian Reform Beneficiaries within Third World economic and poverty conditions. Governance principles can be applied as implementation strategies of Official Development Assistance (ODA)-assisted microfinance program as a tool for poverty reduction and development. In view of the Philippine government's limitations, economic and fiscal challenges, the financial and technical support programs of the international donor community provide a big boost to the effectiveness and impact of microfinance in reducing the incidents of poverty in Third World countries such as the Philippines. As a tool for poverty reduction, microcredit is applicable only to the enterprising poor based on Joe Remenyi's (1999) Poverty Pyramid which is a useful tool for the application of BRAC's graduated strategy for helping the poor when they are grouped into: (1) micro-enterprise operators or the less poor, (2) enterprising or moderately poor, (3) laboring or very poor, and (4) poorest of the poor and most vulnerable or the ultra-poor. The use of microcredit to assist poverty groups is recommended to be based on existing livelihood activities and micro-entrepreneurial skills and capabilities. Furthermore, the program design of the Bangladesh Rural Advancement Committee (BRAC) is found to be appropriate for the agrarian reform beneficiaries in Zamboanga Peninsula (Region IX), Philippines.
Keywords: A; M; J; P; 330; microcredit; microfinance; governance; poverty; Mindanao; Philippines